Actualisation of Inclusive Values Through Religious Education in High Schools - Bahdar Bahdar; Saepudin Mashuri; Rusdin Rusdin; Rusmin Rusmin; Amir Basir Zanki (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
This study aims to analyse the actualisation of inclusive values in religious learning and examine how the values of tasamuh, ta'awun, and justice are applied at SMA Karuna Dipa Palu, which has a diversity of ethnicities, cultures, and religions. The main objective is to assess how these values strengthen inclusive religious education and identify opportunities and challenges in their implementation. This study uses a qualitative field study method with a case study approach, collecting data through interviews, observations, and documentation analysis to understand the application of inclusivism values in religious education at Karuna Dipa High School, with data analysis carried out using the Miles and Huberman techniques which include data condensation, data presentation, and concluding. The formal-textual approach in religious learning actualises the values of inclusivity through the opening, core, and closing stages. In the opening stage, teachers from various religions prepare the class and motivate students. In the core stage, the values of openness, tolerance, mutual assistance, and justice are taught through each religion's teachings. In the closing stage, teachers and students summarise necessary materials and give assignments, thus creating solid social solidarity in the school. Karuna Dipa High School faces challenges in developing inclusivism values, such as limited technological resources, visualisation facilities for materials, and limited learning time. In addition, the lack of sustainable religious programs also hinders students' comprehensive understanding of inclusivism. This research implies that inclusivism values in religious education can strengthen social solidarity and inclusivity in diverse schools but requires increased resources, facilities, and sustainable programs for optimal results.